VALVE BRONCHIAL BLOCK IN THE INTEGRATED TREATMENT OF BRONCHIAL PLEURAL FISTULAS AFTER SURGICAL REDUCTION OF PULMONARY VOLUME - E. A. Tseymakh; K. K. Kozlov; V. M. Gershevich; A. V. Levin; M. S. Korzhuk; E. Zh. Kopin (Туберкулез и болезни лёгких)
Formation of bronchopleural fistulas after surgical reduction of pulmonary volume is one of the most frequent complications of surgical treatment of pulmonary emphysema. In order to control bronchopleural fistulas in the patients after surgical reduction of pulmonary volume the technique of valve bronchial block has been o}ered. This technique has been applied in 7 patients, and the favorable outcomes have been achieved in 6 (85.7%) patients. The use of endobronchial valve for occlusion of fistulous bronchi allowed stopping air leaking through drainages, reducing time for pleural cavity drain and decreasing duration of patients' hospital stay.